Sodium silicate-based full-life super-amphiphobic radiation refrigeration block material and preparation method thereof

By transforming the superhydrophobic function from a two-dimensional coating to a three-dimensional bulk material, a macro-micro-nano three-level rough structure and a three-dimensional silicon-oxygen network framework are constructed, solving the mechanical wear and contamination problems of radiation-cooled coatings and achieving stable performance and self-cleaning function throughout the entire lifespan.

CN120903906APending Publication Date: 2025-11-07WUHAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511109355.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing polymer-based radiation cooling coatings are prone to peeling under mechanical wear and thermal stress, making it difficult to meet the long life requirements of building envelope materials. At the same time, surface contaminants are easy to adhere to, leading to the degradation of optical performance.

Method used

The superhydrophobic and amphoteric properties are transformed from two-dimensional coatings to three-dimensional bulk materials. Through cross-scale structural design and chemical bonding reinforcement, a macro-micro-nano three-level rough structure is constructed. Combined with a three-dimensional silicon-oxygen network framework, the mechanical durability and superhydrophobic and amphoteric properties of the material are improved.

Benefits of technology

It achieves stable performance of radiation cooling materials throughout their entire life cycle, reduces maintenance costs, possesses excellent durability and self-cleaning function, adapts to harsh environments, and reduces cleaning energy consumption and water resource consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a water glass-based full-life super-amphiphobic radiation refrigeration block material, which is prepared from the following raw materials in parts by weight: 1.5 to 3 parts of C-F long-chain modified micro-nano particles, 0.5 to 1.5 parts of water glass-based binder, 0.1 to 0.3 part of nano silicon dioxide sol and 0.05 to 0.16 part of curing catalyst, the C-F long-chain modified micro-nano particles are obtained by sequentially carrying out silane coupling agent grafting modification and fluorosilane grafting modification on nano particles with high sunlight reflectivity and micro particles with high sunlight emissivity. The super-amphiphobic function is converted into a three-dimensional block material from a two-dimensional coating, stress distribution optimization and interface bonding energy improvement are achieved while the ultra-low surface energy characteristic is kept, the problems of optical performance degradation and the like caused by surface pollution of the radiation refrigeration material are effectively solved, the mechanical durability of the material is essentially improved, and the service life of the radiation refrigeration material is prolonged. And the radiation refrigeration system can maintain stable performance in the whole life cycle.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of functional materials, and particularly relates to a sodium silicate-based full-life super-amphiphobic radiative cooling block material and a preparation method thereof. BACKGROUND

[0002] Radiative cooling technology provides a zero-energy consumption cooling solution for the building field by selectively reflecting sunlight and efficiently radiating heat to outer space, which can effectively alleviate the air conditioning cooling burden accounting for more than 40% of global building energy consumption. However, the current widely used polymer-based radiative cooling coating has a serious functional degradation problem: the hydrophilicity of the surface leads to easy adhesion and accumulation of pollutants, which significantly reduces the optical reflection performance; more importantly, the micro-nano composite structure of the traditional coating is prone to interface peeling under the action of mechanical wear, temperature stress and the like, and is difficult to meet the long-life requirement of building envelope materials.

[0003] Endowing the material with super-amphiphobicity (simultaneously hydrophobic and oleophobic) is considered to be an ideal way to realize a self-cleaning radiative cooling surface, but the traditional implementation method relies on the design of brittle micro-nano structures, which is easy to be physically damaged under complex outdoor conditions, causing the failure of super-amphiphobicity. The root cause of this contradiction lies in the inherent conflict between mechanical strength and surface functionality in the two-dimensional coating system: improving wear resistance requires strengthening the material density, while building super-amphiphobicity requires maintaining an open multi-level rough structure, which is difficult to effectively compatible in the traditional material system. SUMMARY

[0004] The main purpose of the present application is to solve the problems and deficiencies existing in the prior art, and to provide a super-amphiphobic radiative cooling block material, which changes the super-amphiphobic function from a two-dimensional coating to a three-dimensional block material, and realizes stress distribution optimization and interface bonding energy improvement while maintaining ultra-low surface energy characteristics through cross-scale structure design and chemical bonding strengthening, effectively solving the problem of optical performance decay caused by surface pollution of the radiative cooling material, and essentially improving the mechanical durability of the material, so that the radiative cooling system maintains stable performance throughout its life cycle.

[0005] To achieve the above purpose, the technical scheme adopted by the present application is as follows: A sodium silicate-based full-life super-amphiphobic radiative cooling block material, each raw material and the weight percentage thereof include: C-F long-chain modified micro-nano particles 1.5-3 parts, a sodium silicate-based binder 0.5-1.5 parts, nano-silica sol 0.1-0.3 parts, and a curing catalyst 0.05-0.16 parts; the C-F long-chain modified micro-nano particles are obtained by successively grafting modification with a silane coupling agent and a fluorosilane on high-solar reflectance nano-particles and high-solar emissivity micro-particles.

[0006] In the scheme, the surface roughness Ra of the water glass-based all-life super-amphiphobic radiation block material is 3-10 μm.

[0007] In the scheme, the particle size of the high-solar reflectance nanoparticles is 20-200 nm; and the particle size of the high-solar emissivity microparticles is 1-20 μm.

[0008] In the scheme, the high-solar reflectance nanoparticles can be selected from one or more of TiO2 (anatase phase), BaSO4, CaCO3, ZnO, BaTiO3, Al2O3, etc., and the high-solar reflectance spectral range is 300-2500 nm; and the high-solar emissivity microparticles can be selected from one or more of hexagonal boron nitride (h-BN), Al2SiO5, MgO, SiO2, hollow glass beads, etc., and the high-solar emissivity range is 7-15 μm.

[0009] Further, the mass ratio of the high-solar reflectance nanoparticles to the high-solar emissivity microparticles is 1-5:1-10.

[0010] In the scheme, the silane coupling agent can be selected from one or more of KH550, KH560, KH570, etc., and the total mass of the micro-nanoparticles (high-solar reflectance nanoparticles and high-solar emissivity microparticles) is 1.5-2.5%.

[0011] In the scheme, the fluorosilane can be selected from one or more of perfluorooctyltrimethoxysilane, perfluorooctyltriethoxysilane, perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, 1H,1H,2H,2H-perfluorohexyltriethoxysilane, etc.

[0012] In the scheme, the mass ratio of the fluorosilane to the total mass of the micro-nanoparticles (high-solar reflectance nanoparticles and high-solar emissivity microparticles) is 1:10-40.

[0013] Further, the preparation step of the C-F long-chain modified micro-nanoparticles includes the following: mixing the high-solar reflectance nanoparticles and the high-solar emissivity microparticles, ultrasonic dispersion (0.5-2 h) in an organic solvent (alcohol solvent, etc.), adding a silane coupling agent and adjusting the pH to 10-11, and then stirring at a constant temperature of 50-60 o C for 2-4 h to form a siloxane grafting layer on the surface of the particles through a surface hydroxylation reaction, thereby improving the interfacial bonding force with the water glass matrix; then mixing with fluorosilane, ultrasonic dispersion (0.5-1 h), and drying treatment (60-120 oC, 12~24 h), the fluorosilane molecules are grafted to the surface of the micro-nano particles through the silicon-oxygen bond to form a C-F long chain to reduce the surface energy, and the C-F long chain modified micro-nano particles are obtained.

[0014] In the above scheme, the water glass-based binder can be specifically one or more of liquid sodium silicate, liquid potassium silicate, liquid lithium silicate, etc.

[0015] In the above scheme, the modulus of the water glass-based binder is 2~3.5 (Baume 32~45°Bé).

[0016] In the above scheme, the solid content of the nano-silica sol is 35~50%.

[0017] In the above scheme, the solidification catalyst can be selected from one or more of triammonium citrate, sodium fluorosilicate, calcium chloride, magnesium chloride, sodium metasilicate, potassium silicate, etc.

[0018] Further, the amount of the solidification catalyst is 5~15% of the mass of the water glass-based binder.

[0019] The application also provides a preparation method of the above-mentioned water glass-based full-life super-amphiphobic radiation refrigeration block material, comprising the following steps: (1) mixing the weighed water glass-based binder with the C-F long chain modified micro-nano particles, and introducing the nano-silica sol to construct a nano-scale pore network in the water glass matrix during the subsequent gel solidification process, thereby improving the flexibility and shrinkage resistance of the matrix; finally, adding a solidification catalyst and stirring to form a homogeneous slurry (white viscous slurry); (2) vacuum injection molding of the obtained homogeneous slurry under ultrasonic conditions, keeping the vacuum environment stationary (15~30 min) to ensure uniform filling of the slurry in the mold structure, and room temperature solidification; the solidified mold is placed in a low-temperature environment for freezing (10~40 min) to reduce the interfacial adhesion by utilizing the difference in the thermal expansion coefficients of the mold (which can be selected from PTFE, etc.) and the block material, thereby achieving damage-free demolding; (3) vacuum drying of the demolded block material to remove internal free water and retain the nano-scale pore network; then polishing (processing rough microgrooves) the surface of the block material to form a multi-level rough structure with the surface of the nanometer particles modified by fluorides, thereby obtaining the water glass-based full-life super-amphiphobic radiation refrigeration block material.

[0020] In the above scheme, the stirring step in step (1) is performed at a rate of 200~1000 rpm for 5~20 min.

[0021] In the above scheme, the vacuum injection molding in step (2) uses a vacuum degree of 0.06-0.08 MPa and a flow rate of 2-6 mL / min; and uses an ultrasonic power of 200-2000 W.

[0022] In the above scheme, the room temperature curing time in step (2) is 2-10 days.

[0023] In the above scheme, the low-temperature environment in step (2) is -40--15 o C.

[0024] In the above scheme, the vacuum drying temperature is 40-60 o C, the vacuum degree is 0.08-0.1 MPa, and the time is 2-20 h.

[0025] In the above scheme, the polishing step polishes the surface of the cold block material to a roughness Ra of 3-10 μm.

[0026] Further, the polishing step can use sandpaper polishing and the like.

[0027] The super-amphiphobic radiation refrigeration block material prepared according to the above scheme has a water contact angle of up to 165 o , a water rolling angle of up to 2 o , an oil contact angle of up to 155 o , an oil rolling angle of up to 6 o , and both the surface and the inner cross section can exhibit excellent super-amphiphobic properties. The prepared super-amphiphobic radiation refrigeration block material is subjected to a compressive strength test, and the compressive strength of a 2×2×2 cm 3 standard sample can be up to 34 MPa; after 18000 cycles of friction and wear tests, the water droplet contact angle is still greater than 159 o , the rolling angle is less than 4 o , the oil droplet contact angle is greater than 154 o , and the rolling angle is less than 8 o . The prepared super-amphiphobic radiation refrigeration block material is irradiated by a xenon lamp light source (model CEL-S500-T5) to simulate sunlight (light intensity of 100 mW / cm 2 ), and the temperature can be reduced by 6.5 o C compared with the air environment, showing excellent radiation refrigeration performance.

[0028] The principles of the present application include: (1) Core role of C-F long-chain modified micro-nano particles Low surface energy: C-F long chains have extremely low surface energy, and after being anchored on the surface of micro-nano particles through chemical bonds, a relatively ordered "fluorocarbon layer" is formed, and the molecular chains are in a close-packed conformation (similar to "molecular shield"), which thermodynamically repels water and oil infiltration; The basic framework of the multi-scale rough structure: the micron-nano scale stepped rough structure formed by the introduction of micro and nano particles, combined with the macro grooves formed by subsequent surface polishing, constructs a macro-micro-nano three-level rough structure to enhance the superhydrophobic and dihydrophobic properties. Ensuring the performance of the inner cross section: The modified micro-nanoparticles are uniformly dispersed in the matrix (achieved through ultrasonic vacuum molding), so that when any cross section inside the bulk material is fractured, the exposed particle surface has CF long chains, and the internal nanoporous network (not destroyed by vacuum drying) forms an internally dispersed rough structure. Even if local damage occurs (such as collision cracks or cutting to form a new cross section), the exposed internal structure can still maintain superhydrophobicity and prevent liquid from seeping into the material through the damaged area, thus greatly extending the service life of the material. This breaks through the limitation of traditional superhydrophobic materials that are only effective on the surface and simultaneously achieves the effective construction of superhydrophobic properties of the inner cross section.

[0029] (2) Structured construction of three-dimensional silicon-oxygen network framework The three-dimensional silica-oxygen network is formed by water glass (silicate), micro / nano fillers, and nano-silica sol. The introduced micro / nano fillers have a large specific surface area (especially the nanoparticles) and a large number of hydroxyl groups (such as Al-OH) on their surface. These hydroxyl groups easily dissociate into H+ in an alkaline environment (the water glass system is alkaline). + This forms negatively charged active sites (Al-O). - ), and silanol (Si-OH) or silicate ions (SiO3) in water glass 2- Nucleophilic reactions occur, forming Si-O-Al covalent bonds that anchor alumina particles to silicon-oxygen chains, making the micro / nano particles nodes in the network. Furthermore, multiple Al-OH groups on the alumina particle surface can simultaneously react with multiple silicon-oxygen chains, promoting the transformation of linear silicon-oxygen chains into a three-dimensional network, forming a dense three-dimensional silicon-oxygen network (other micro / nano fillers exhibit similar reactions). The introduced nano-SiO2 particles (high specific surface area, multiple silanol groups) can react with silicate ions (SiO3) in water glass. 2- The Si-O-Si bond condensation reaction occurs, refining the network structure and reducing volume shrinkage during water glass curing (traditional water glass is prone to cracking due to shrinkage during curing). Therefore, in this invention, micron-sized particles (such as micron-sized alumina or hollow glass microspheres) serve as the macroscopic framework, uniformly dispersed in the silicon-oxygen network. Their surfaces are bonded to the surrounding silicon-oxygen chains through Si-O-Al bonds, enabling them to withstand external stresses (such as tensile forces generated by curing shrinkage) and improving the compressive strength of the network. The gaps between the micron-sized particles are filled by the nano-silicon-oxygen network, forming a multi-level structure of "micron-framework-nano-filler," simultaneously improving the rigidity and toughness of the three-dimensional network.

[0030] Retention of nanoscale pore network: By removing free water through vacuum drying (non-traditional high-temperature drying), the nanoscale pores formed during the gelation process (pore size matching infrared radiation wavelength) are retained, both maintaining the rough structure constructed by micro-nano particles (the pores themselves are also part of the roughness) and achieving radiation cooling performance through the low thermal conductivity of air pores and infrared radiation enhancement.

[0031] (3) Synergistic regulation between components Interface compatibility of water glass and modified micro-nano particles: Water glass (polar silicate) is hydrophilic by itself, while the C-F chain on the surface of the modified particles is hydrophobic. Through the bridging effect of nanosilica sol (silanol both condenses with water glass and reacts with residual hydroxyl groups on the particle surface), the dispersibility of the particles in the matrix is improved, effectively avoiding problems such as agglomeration; Matching of curing catalyst and freeze demolding: Sodium fluorosilicate and other curing catalysts control the gelation rate to ensure good fluidity of the slurry during vacuum injection molding, while low-temperature freezing takes advantage of the difference in thermal expansion coefficient between PTFE molds and blocks to avoid damage to the surface or internal structure during demolding, ensuring the integrity of the rough structure and modified layer.

[0032] Compared with the prior art, the beneficial effects of the present application include: (1) By chemical interface regulation through nanoscale particle surface hydroxylation-fluoride modification and combined with physical structure design of the three-dimensional siloxane network skeleton, a macro-micro-nano three-level rough structure is constructed to strengthen the super-amphiphobic performance, breaking through the technical bottleneck that traditional radiation cooling materials cannot simultaneously achieve mechanical performance and functional performance (super-amphiphobicity, radiation cooling, etc.); (2) The three-dimensional siloxane C-F long-chain modified micro-nano particle network structure formed by curing can significantly enhance the hardness and interfacial bonding strength of the obtained composite material, overcoming the defects of traditional coatings such as easy wear, delamination, and peeling, greatly reducing building maintenance costs; and can simultaneously construct good super-amphiphobic properties on the surface and internal cross-section of the obtained block material, ensuring excellent durability; (3) Room temperature curing technology, no need for high-temperature sintering or high-energy consumption equipment, no organic volatile emissions during production process, meeting the development needs of the building industry for low carbonization and industrialization; (4) The formulation system mainly composed of inorganic components endows the obtained block material with good ultraviolet resistance, acid and alkali corrosion resistance, and fireproof properties, which can adapt to harsh environments such as coastal areas and industrial areas, while also having radiation cooling and self-cleaning functions, reducing building surface cleaning energy consumption and water resource consumption. BRIEF DESCRIPTION OF DRAWINGS

[0033] Figure 1 Optical photograph of the surface of the sodium silicate water glass-based full-life super-amphiphobic radiation cooling block material obtained in Example 1, as well as water and oil contact angle photographs; Figure 2The optical photo and water, oil contact angle photo of the sodium silicate water glass based all-life super-amphiphobic radiative cooling bulk material obtained in Example 1 at any cross section; Figure 3 The structural schematic diagram of the indoor simulation radiative cooling test device; Figure 4 The sodium silicate water glass based all-life super-amphiphobic radiative cooling bulk material obtained in Example 1 is irradiated by a xenon lamp light source to simulate a sunlight (the light intensity is 100 mW / cm 2 ) irradiation, and the temperature change of the bulk material is recorded by a thermocouple in real time. Figure 5 From left to right, they are the weather condition of outdoor actual operation, the device photo, and the ambient temperature change and the bottom temperature change of the super-amphiphobic radiative cooling bulk material recorded by a thermocouple in real time; Figure 6 The water contact angle / rolling angle and oil contact angle / rolling angle evolution curves of the sodium silicate water glass based all-life super-amphiphobic radiative cooling bulk material prepared in Example 1 subjected to mechanical wear test; Figure 7 The sodium silicate water glass based all-life super-amphiphobic radiative cooling bulk material obtained in Example 2 is irradiated by a xenon lamp light source to simulate a sunlight (the light intensity is 100 mW / cm 2 ) irradiation, and the temperature change of the bulk material is recorded by a thermocouple in real time. Figure 8 The water contact angle / rolling angle and oil contact angle / rolling angle evolution curves of the sodium silicate water glass based all-life super-amphiphobic radiative cooling bulk material prepared in Example 2 subjected to immersion test in an HCl solution with pH of 13; Figure 9 The optical photo and water, oil contact angle photo of the sodium silicate water glass based all-life super-hydrophobic radiative cooling bulk material obtained in Comparative Example 1; Figure 10 The sodium silicate water glass based all-life super-hydrophobic radiative cooling bulk material obtained in Comparative Example 1 is irradiated by a xenon lamp light source to simulate a sunlight (the light intensity is 100 mW / cm 2 ) irradiation, and the temperature change of the bulk material is recorded by a thermocouple in real time. DETAILED DESCRIPTION

[0034] The technical solutions adopted in the present application will be described in detail below through specific implementation examples, which are only a part of the present application and do not represent all embodiments. Unless otherwise specified, the experimental methods adopted in the present application are conventional methods, and the instruments and equipment adopted are commercial products in the technical field.

[0035] Example 1 A sodium silicate water glass-based full-life super-amphiphobic radiative refrigeration block material, and a preparation method thereof, the preparation method comprising the following steps: (1) 13.6 g (10 g as 1 part by weight) of a sodium silicate water glass solution (40°Bé Baume) with a modulus of 3.3 is taken, mixed with 24 g of C-F long-chain modified micro-nano particles, and 2 g of nano-silica sol (solid content 50%) is introduced, and finally 1.36 g of sodium fluorosilicate curing agent is added, uniformly dispersed in a high-speed mixer at a speed of 800 rpm for 10 min, to form a homogeneous slurry; The preparation method of the C-F long-chain modified micro-nano particles comprises the following steps: 20 g of nano-Al2O3 particles with an average particle size of 30 nm and 4 g of hollow glass microbead microparticles with an average particle size of 10 μm are mixed in a mass ratio of 5:1, then ultrasonic dispersion is performed in 100 ml of ethanol for 1 h (power 300 W, temperature 35 ℃), 0.5 g of silane coupling agent KH550 is added, a 1.8 M NaOH solution is used to adjust the pH value of the obtained mixed solution to 10-11, and mechanical stirring is performed in a 60 ℃ constant temperature water bath for 2 h to obtain a siloxane grafted modified micro-nano particle dispersion liquid; full-fluorodecyltrimethoxysilane (1H, 1H, 2H, 2H-full-fluorodecyltrimethoxysilane; and the mass ratio of micro-nano particles to fluorosilane is 10:1) is added to the dispersion liquid and ultrasonic dispersion is performed for 1 h, and then vacuum drying is performed in a 80 ℃ vacuum drying box for 12 h, so that the fluorosilane molecules are grafted on the surface of the nano-particles through siloxane bonds, to obtain C-F long-chain modified micro-nano particles; (2) The obtained homogeneous slurry is poured into an injection mold cavity with a flow guide groove, a vacuum injection molding system (vacuum degree 0.08 MPa) is started, PTFE molds (2×2×2 cm 3 ) are injected from the bottom flow guide groove at a rate of 5 mL / min, while ultrasonic vibration (power 200 W) of 100 Hz is applied to break the micro-bubbles in the slurry by cavitation effect; after the injection molding is completed, the vacuum environment is maintained for 20 min to ensure that the slurry uniformly fills the mold structure, and finally natural room temperature curing is performed for 3 days; The cured mold is placed in a-30 ℃ environment for 30 min, the difference in the thermal expansion coefficients of the PTFE mold and the block material is used to reduce the interfacial adhesion, and damage-free demolding is achieved; (3) The demolded block material is vacuum dried (temperature 50 o C, vacuum degree 0.08 MPa, time 4 h) to remove the internal free water and retain the nano-scale pore network; The smooth surface of the formed block is polished rough by using 120 mesh sandpaper, the arithmetic square deviation Ra of the surface roughness is 3-10 μm, a multi-level rough structure is formed on the surface of the nano-particles modified by fluorides in the early stage, and finally the super-amphiphobic property is realized.

[0036] Figure 1 The optical photos and water, oil contact angle photos of the surface of the sodium silicate water glass-based full-life super-amphiphobic radiative cooling bulk material obtained in the embodiment show that the methylene blue dyed water droplets and transparent oil droplets on the surface of the bulk material are in a shrinking state, and the water, oil contact angles are 162 o and 152 o , respectively, showing excellent super-amphiphobic properties.

[0037] Figure 2 The optical photos and water, oil contact angle photos of the section of the sodium silicate water glass-based full-life super-amphiphobic radiative cooling bulk material obtained in the embodiment show that the methylene blue dyed water droplets and transparent oil droplets on the surface of the bulk material are in a shrinking state, and the water, oil contact angles are 164 o and 155 o , respectively, and the bulk material also shows excellent super-amphiphobic properties.

[0038] Figure 3 The schematic diagram of the indoor simulated radiative cooling test device is shown in the figure, a xenon lamp (model CEL-S500-T5) is used to simulate sunlight (light intensity is 100 mW / cm 2 ), the prepared super-amphiphobic radiative cooling bulk material is irradiated, a thermocouple is used to detect the temperature rise of the bottom surface of the sample, the size of the sample in the figure is 3.5*3.5*0.5 cm, and the radiative cooling performance of the sample is verified by comparing with the ambient air temperature or wood and ordinary concrete test blocks.

[0039] Figure 4 The sodium silicate water glass-based full-life super-amphiphobic radiative cooling bulk material obtained in the embodiment is irradiated by a xenon lamp (model CEL-S500-T5) to simulate sunlight (light intensity is 100 mW / cm 2 ), and a thermocouple is used to record the temperature change of the bulk material in real time to test the temperature rise of the bottom of the bulk material. Figure 4 It can be known that under 1 sun intensity, the ambient temperature rises from 28.3°C to 36.7°C in 750 seconds; the temperature of the bottom of the wood rises from 28.3°C to 43.6°C; the temperature of the bottom of the ordinary concrete rises from 27.5°C to 48.6°C, while the sodium silicate water glass-based full-life super-amphiphobic radiative cooling bulk material prepared in the embodiment only rises from 26.6°C to 30.4°C, and the increase is only 3.8°C. Compared with the ambient temperature, the wood temperature and the concrete temperature, the present application can realize temperature reduction of 6.3°C, 13.2°C and 18.2°C, respectively. The results show that the super-amphiphobic radiative cooling bulk material prepared in the present application has excellent radiative cooling performance.

[0040] Figure 5The outdoor actual operation weather, device photos, and real-time recorded ambient temperature changes and bottom temperature changes of the superamphiphobic radiative cooling block material are shown in Figure 5 It can be seen that, in sunny weather (average light intensity of 76 mW / cm 2 ), the ambient temperature rises to a maximum of 28.3°C within 1200 seconds, while the maximum temperature of the sodium silicate water glass-based full-life superamphiphobic radiative cooling block material prepared in this embodiment is only 23°C. Compared with the ambient temperature, the present application can achieve a temperature drop of 5.3°C in outdoor actual operation. The results show that the superamphiphobic radiative cooling block material prepared in the present application can exhibit excellent radiative cooling performance in an outdoor environment.

[0041] Figure 6 The water contact angle / roll angle and oil contact angle / roll angle evolution curves of the sodium silicate water glass-based full-life superamphiphobic radiative cooling block material prepared in this embodiment were tested by a Taber 5135 type friction and wear tester under a load of 250 g using an H-18 (non-elastic ceramic material) grinding wheel. As can be seen from the figure, after 18000 cycles, the water droplet contact angle is still greater than 159 o , and the roll angle is less than 4 o ; the oil droplet contact angle is greater than 154 o , and the roll angle is less than 5 o , showing excellent superamphiphobic performance and outstanding wear resistance and durability, which embodies the essential improvement of the mechanical durability of superhydrophobic materials in the present application, and enables the radiative cooling system to maintain stable performance throughout its life cycle.

[0042] Example 2 A potassium silicate water glass-based full-life superamphiphobic radiative cooling block material, the preparation method thereof comprising the following steps: (1) 13.6 g (10 g as 1 part by weight) of a potassium silicate water glass solution (40°Bé Baume) with a modulus of 3.3 is mixed with 30 g of C-F long-chain modified micro-nano particles, and 1 g of nano-silica sol (solid content 50%) is introduced, and finally 1.36 g of sodium fluorosilicate curing agent is added, and the homogeneous slurry is uniformly dispersed in a high-speed stirrer at a speed of 800 rpm for 15 min; The preparation method of the C-F long chain modified micro-nano particles includes the following steps: 15 g of nano TiO2 particles with an average particle size of 50 nm and 15 g of SiO2 microparticles with an average particle size of 20 μm are selected, mixed according to a mass ratio of 1:1, and then placed in 100 ml of ethanol for ultrasonic dispersion for 2 h (power 300 W, temperature 35 ℃). 0.5 g of silane coupling agent KH550 is added, and the pH value of the obtained mixed solution is adjusted to 10-11 by using a 1.8 M NaOH solution. The solution is mechanically stirred in a 60 ℃ constant temperature water bath for 4 h to obtain siloxane grafted modified micro-nano particles. The pH value is adjusted to 10-11, and the solution is mechanically stirred in a 60 ℃ constant temperature water bath for 2 h to obtain a siloxane grafted modified micro-nano particle dispersion liquid. Full-fluorodecyltrimethoxysilane (micro-nano particles and fluorosilane in a mass ratio of 10:1) is added to the dispersion liquid and ultrasonically dispersed for 1.5 h, and then treated in a 80 ℃ vacuum drying oven for 12 h to graft fluorosilane molecules onto the surface of the nano particles through siloxane bonds to obtain C-F long chain modified micro-nano particles. (2) The obtained homogeneous slurry is poured into an injection mold cavity with a flow guide groove, and a vacuum injection molding system (vacuum degree 0.06 MPa) is started. PTFE mold (2×2×2 cm 3 ) is injected at a rate of 5 mL / min through the bottom flow guide groove, and at the same time, ultrasonic vibration (power 200 W) of 100 Hz is applied to break the micro-bubbles inside the slurry by cavitation effect. After injection molding, the vacuum environment is maintained for 30 min to ensure that the slurry fills the mold structure uniformly, and finally it is naturally cured at room temperature for 5 days; The cured mold is placed in a-30 ℃ environment for 40 min to reduce the interfacial adhesion by utilizing the difference in thermal expansion coefficient between the PTFE mold and the bulk material, and to achieve non-damage demolding; (3) The demolded bulk material is vacuum dried (temperature 60 o C, vacuum degree 0.08 MPa, time 6 h) to remove the internal free water and retain the nano-scale pore network; The smooth surface of the formed bulk is roughened by using 120 mesh sandpaper, and the arithmetic square deviation Ra of the surface roughness is 3-10 μm, which forms a multi-level rough structure with the surface of the fluorine-modified nano particles, and finally realizes the super-amphiphobic property.

[0043] Figure 7 A xenon lamp (model CEL-S500-T5) is used to simulate sunlight (light intensity 100 mW / cm 2 ) to irradiate the potassium silicate water glass-based full-life super-amphiphobic radiation refrigeration bulk material obtained in this embodiment, and a thermocouple is used to record the temperature change of the bulk material in real time to test the temperature rise at the bottom of the bulk material. From the Figure 7It can be seen that under 1 sun intensity, the ambient temperature rises from 28.3°C to 36.7°C within 750 seconds; the wood bottom temperature rises from 28.3°C to 43.6°C; the ordinary concrete bottom temperature rises from 27.5°C to 48.6°C, while the potassium silicate water glass-based full-life super-amphiphobic radiative cooling block material prepared in the embodiment only rises from 26.8°C to 30.2°C, with an increase of only 3.4°C. Compared with the ambient temperature, wood temperature and concrete temperature, the present application can achieve a temperature drop of 6.5°C, 13.4°C and 18.4°C, respectively. It can be seen that the super-amphiphobic radiative cooling block material prepared in the present application has excellent radiative cooling performance.

[0044] Figure 8 The water contact angle / roll angle and oil contact angle / roll angle evolution curves of the potassium silicate water glass-based full-life super-amphiphobic radiative cooling block material prepared in the embodiment subjected to the immersion test of the HCl solution with a pH of 13 are shown in the figure. It can be seen from the figure that after 50 days of immersion, the water droplet contact angle is still greater than 160 o , the roll angle is less than 3 o ; the oil droplet contact angle is greater than 152 o , the roll angle is less than 6 o , showing excellent super-amphiphobic performance and excellent chemical corrosion resistance, embodying the essential improvement of the present application on the durability of super-hydrophobic materials, so as to maintain the stable performance of the radiative cooling system in the full life cycle.

[0045] Comparative Example 1 A preparation method of a sodium silicate water glass-based radiative cooling block material, comprising the following steps: (1) 27.2 g (10 g as 1 part by weight) of sodium silicate water glass solution (40°Bé Baume) with a modulus of 3.3 is mixed with 24 g of C-F long-chain modified micro-nano particles (preparation method same as Example 1), and 2 g of nano-silica sol (solid content 50%) is introduced, and finally 2.72 g of sodium fluorosilicate curing agent is added, uniformly dispersed in a high-speed stirrer at a speed of 800 rpm for 10 min to form a homogeneous slurry; (2) Pour the obtained homogeneous slurry into the injection mold cavity with a flow guide groove, start the vacuum injection molding system (vacuum degree 0.06 MPa), inject PTFE mold (2×2×2 cm 3 ) through the bottom flow guide groove at a rate of 5 mL / min, and at the same time, apply ultrasonic vibration of 100 Hz (power 200 W) to break the micro-bubbles in the slurry by cavitation effect; after injection molding, keep the vacuum environment for 20 min, ensure that the slurry fills the mold structure uniformly, and finally naturally solidify at room temperature for 3 days; After the mold is cured, it is placed in a -30 °C environment for 30 min to freeze, and the difference in thermal expansion coefficient between the PTFE mold and the block material reduces the interfacial adhesion to achieve non-damage demolding; (3) The demolded block material is vacuum dried (temperature 60 o C, vacuum degree 0.08 MPa, time 6 h) to remove internal free water and retain the nanoscale pore network; The smooth surface of the formed block is polished rough with 120 mesh sandpaper, and the arithmetic square deviation Ra of the surface roughness is in the range of 3-10 μm, forming a multi-level rough structure with the surface of the fluorine-modified nanoparticles, and finally realizing the super-hydrophobic property.

[0046] Figure 9 The optical photos and water and oil contact angle photos of the surface of the sodium silicate water glass-based full-life super-hydrophobic radiation refrigeration block material obtained in this comparative example can be seen that the methylene blue dyed water droplets on the surface of the block material show a shrinking state, while the transparent oil droplets on the surface of the block material can only show a semi-shrinking state, and the water and oil contact angles are 154 o and 130 o respectively. Compared with Example 1, due to the high proportion of water glass added in this comparative example, the surface energy threshold of the block material system is significantly improved, resulting in that its interface characteristics only show a single super-hydrophobic effect, and the double-repellent function of the liquid-liquid interface cannot be realized, so it only shows super-hydrophobic property, but not super-amphiphobic property.

[0047] Figure 10 A xenon lamp (model CEL-S500-T5) is used to simulate a sunlight (light intensity is 100 mW / cm 2 ) to irradiate the sodium silicate water glass-based full-life super-hydrophobic radiation refrigeration block material obtained in this comparative example, and a thermocouple is used to record the temperature change of the block material in real time to test the temperature rise at the bottom of the block material. From the Figure 10It can be seen that under 1 sun intensity, the ambient temperature rises from 28.3°C to 36.7°C in 750 seconds; the wood bottom temperature rises from 28.3°C to 43.6°C; the ordinary concrete bottom temperature rises from 27.5°C to 48.6°C, while the sodium silicate water glass-based full-life super-hydrophobic radiative cooling block material prepared in the present comparison example rises from 27.1°C to 33.7°C, an increase of 6.6°C. Compared with the ambient temperature, wood temperature and concrete temperature, the present application can achieve a temperature drop of 3°C, 9.9°C and 14.9°C, respectively. Compared with Example 1, the refrigeration performance is greatly reduced, which is due to the high proportion of water glass added in the present comparison example, which forms a dense coating with the micro-nano particles having high solar reflectance and thermal emission characteristics, significantly reducing the surface exposure and effective concentration of functional particles, ultimately leading to a stepwise decay of the radiative cooling efficiency of the system.

[0048] Comparative Example 2 A preparation method of a sodium silicate water glass-based radiative cooling block material, comprising the following steps: (1) 3 g (10 g as 1 part by weight) of sodium silicate water glass solution (40°Bé Baume) with a modulus of 3.3 is mixed with 24 g of C-F long-chain modified micro-nano particles (same as Example 1), and 2 g of nano-silica sol (solid content 50%) is introduced to generate silica in situ in the water glass matrix during subsequent natural curing to construct a nano-scale pore network, improve the flexibility and shrinkage resistance of the matrix, and finally add 0.5 g of sodium fluorosilicate curing agent, uniformly dispersed in a high-speed mixer at a speed of 800 rpm for 10 min to form a homogeneous slurry; (2) Pour the obtained homogeneous slurry into an injection mold cavity with a flow guide groove, start the vacuum injection molding system (vacuum degree 0.06 MPa), and inject PTFE mold (2×2×2 cm 3 ) through the bottom flow guide groove at a rate of 5 mL / min, while applying ultrasonic vibration of 100 Hz (power 200 W) to break the micro-bubbles inside the slurry by cavitation effect; after injection molding, keep the vacuum environment for 20 min to ensure that the slurry fills the mold structure uniformly, and finally naturally cure at room temperature for 3 days; Place the cured mold in a -30°C environment for 30 min to reduce the interfacial adhesion by taking advantage of the difference in thermal expansion coefficients between the PTFE mold and the block material, and achieve damage-free demolding; (3) Vacuum dry (temperature 60 o C, vacuum degree 0.08 MPa, time 6 h) the demolded block material to remove the internal free water and retain the nano-scale pore network; The smooth surface of the formed block is polished rough with 120 mesh sandpaper, and the surface roughness arithmetic square deviation Ra is in the range of 3-10 μm, forming a multi-level rough structure with the surface of the fluorine-modified nanoparticles in the early stage, and finally realizing the super-hydrophobic property.

[0049] Compared with Example 1 and Comparative Example 1, the water glass content of Comparative Example 2 is reduced.

[0050] Comparative Example 3 A sodium silicate water glass-based radiative cooling block material, and a preparation method thereof, includes the following steps: (1) 13.6 g of sodium silicate water glass solution (40°Bé Baume) with a modulus of 3.3 is mixed with 24 g of C-F long-chain modified micro-nano particles (same as Example 1), and 2 g of nano-silica sol (solid content 50%) is introduced, and finally 1.36 g of sodium fluorosilicate curing agent is added, and the homogeneous slurry is uniformly dispersed in a high-speed mixer at a speed of 800 rpm for 10 min; (2) The obtained homogeneous slurry is uniformly poured and filled into a mold structure, and cured at room temperature for 3 days; After the curing is completed, the mold is placed in a-30°C environment for 30 min, and the difference in thermal expansion coefficient between the PTFE mold and the block material is used to reduce the interfacial adhesion, so as to realize damage-free demolding; (3) The demolded block material is vacuum dried (temperature 50 o C, vacuum degree 0.08 MPa, time 4 h) to remove the internal free water and retain the nano-porous network; The smooth surface of the formed block is polished rough with 120 mesh sandpaper, and the surface roughness arithmetic square deviation Ra is in the range of 3-10 μm, forming a multi-level rough structure with the surface of the fluorine-modified nanoparticles in the early stage, and finally realizing the super-hydrophobic property.

[0051] Compared with Example 1, Comparative Example 3 does not use a vacuum injection molding system, but fills the slurry into the mold by manual vibration.

[0052] Comparative Example 4 A sodium silicate water glass-based radiative cooling block material, and a preparation method thereof, includes the following steps: (1) 20 g of nano-Al2O3 particles with an average particle size of 30 nm and 4 g of hollow glass microbeads microparticles with an average particle size of 10 μm were mixed in a mass ratio of 5:1, then 13.6 g of sodium silicate water glass solution (40°Bé Baume) with a modulus of 3.3 was added, then 0.5 g of silane coupling agent KH550 and 1.5 ml of 1.8 M NaOH solution were added, then 2 g of nano-silica sol (solid content 50%) was introduced, then perfluorodecyltrimethoxysilane (microparticles and fluorosilane in a mass ratio of 10:1) was added to modify the microparticles, and finally 1.36 g of sodium fluorosilicate curing agent was added, and the homogeneous slurry was formed by uniformly dispersing in a high-speed stirrer at a speed of 800 rpm for 10 min; (2) The obtained homogeneous slurry was poured into the injection mold cavity with a flow guide groove, and a vacuum injection molding system (vacuum degree 0.08 MPa) was started, and the PTFE mold (2×2×2 cm 3 ) was injected at a rate of 5 mL / min through the bottom flow guide groove, and at the same time, ultrasonic vibration (power 200 W) of 100 Hz was applied to break the micro-bubbles inside the slurry by cavitation effect; After injection molding, the vacuum environment was maintained for 20 min to ensure that the slurry uniformly filled the mold structure, and finally it was naturally cured at room temperature for 3 days; The cured mold was placed in a-30℃ environment for 30 min to reduce the interfacial adhesion by taking advantage of the difference in thermal expansion coefficient between the PTFE mold and the bulk material, and the mold was removed without damage; (3) The bulk material after demolding was vacuum dried (temperature 60 o C, vacuum degree 0.08 MPa, time 4 h) to remove the internal free water and retain the nano-scale pore network; The smooth surface of the formed bulk was polished rough with 120 mesh sandpaper, and the arithmetic square deviation Ra of the surface roughness was in the range of 3~10 μm, which formed a multi-level rough structure with the surface of the nanoparticles modified by fluorides in the early stage, and finally failed to achieve super-amphiphobicity and could only maintain super-hydrophobicity.

[0053] Compared with Example 1, Comparative Example 4 did not modify the microparticles in advance, but prepared the bulk material by blending all raw materials such as fluorosilane and silane coupling agent KH550.

[0054] The performance test results of the sodium silicate water glass-based full-life radiation cooling bulk materials prepared in Examples 1 and Comparative Examples 1~4 are shown in Table 1.

[0055] Table 1 Performance test results of sodium silicate water glass-based full-life radiation cooling bulk materials prepared in Examples 1 and Comparative Examples 1~4

[0056] As can be seen from the above table, by means of multi-scale functional particle collaborative design, the water glass solution is compounded with modified micro-nano optical particles and nano-silica sol, the nano-scale pore network is constructed by means of sol-gel method to enhance the flexibility of the matrix, and a homogeneous system is formed by adjusting the thixotropy of the slurry; the uniform filling of the slurry in the PTFE mold and room temperature curing are realized by means of the vacuum injection molding system and the ultrasonic cavitation effect; after the non-damage demolding is completed by means of the low-temperature thermal peeling technology, the nano-pore structure is reserved by means of vacuum drying, and finally the multi-level rough interface is constructed by means of the surface rough groove processing and the fluoride modification, so that the water glass-based all-life radiation refrigeration block material with high efficient sunlight reflection-emission capacity and super-amphiphobicity is successfully prepared, and the interface bonding strength, the shrinkage resistance and the environmental adaptability are all systematically improved.

[0057] The basic principles, main features and advantages of the present application are shown and described above. It should be understood that the above is only part of the implementation cases of the present application, and is not used to limit the present application. Therefore, any changes and improvements to the above implementation cases should be included in the protection scope of the claims of the present application.

Claims

1. A water glass based all-life-span omniphobic radiative cooling bulk material, characterized in that, The raw materials and the weight percentage thereof include: C-F long chain modified micro-nano particles 1.5-3 parts, water glass-based binder 0.5-1.5 parts, nano-silica sol 0.1-0.3 parts, and curing catalyst 0.05-0.16 parts; the C-F long chain modified micro-nano particles are obtained by sequentially grafting modification of high solar reflectance nano-particles and high solar emissivity micro-particles with silane coupling agent and fluoro-silane.

2. The waterglass-based all-life-span omnidirectional radiative refrigeration bulk material of claim 1, wherein, The particle size of the high solar reflectance nano-particles is 20-200 nm, and the particle size of the high solar emissivity micro-particles is 1-20 μm.

3. The waterglass-based all-life-span omnidirectional radiative refrigeration bulk material of claim 1, wherein, The high solar reflectance nano-particles are one or more of TiO2, BaSO4, CaCO3, ZnO, BaTiO3, and Al2O3, and the high solar reflectance spectral range thereof is 300-2500 nm; the high solar emissivity micro-particles are one or more of hexagonal boron nitride, Al2SiO5, MgO, SiO2, and hollow glass microbeads, and the high solar emissivity range thereof is 7-15 μm.

4. The waterglass-based all-life-span omnidirectional radiative refrigeration bulk material of claim 1, wherein, The mass ratio of the high solar reflectance nano-particles to the high solar emissivity micro-particles is 1-5:1-10.

5. The waterglass-based all-life-span omnidirectional radiative refrigeration bulk material of claim 1, wherein, The fluoro-silane is one or more of perfluorooctyltrimethoxysilane, perfluorooctyltriethoxysilane, perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, and perfluorohexyltriethoxysilane; and the mass ratio of the fluoro-silane to the sum of the high solar reflectance nano-particles and the high solar emissivity micro-particles is 1:10-40.

6. The waterglass-based all-life-span omnidirectional radiative refrigeration bulk material of claim 1, wherein, The water glass-based binder is one or more of liquid sodium silicate, liquid potassium silicate, and liquid lithium silicate.

7. The waterglass-based all-life-span omnidirectional radiative refrigeration bulk material of claim 1, wherein, The solid content of the nano-silica sol is 35-50%.

8. The waterglass-based all-life-span omnidirectional radiative refrigeration bulk material of claim 1, wherein, The curing catalyst is one or more of triammonium citrate, sodium fluosilicate, calcium chloride, magnesium chloride, sodium metasilicate, and potassium silicate.

9. The method for preparing the water glass-based all-life super-amphiphobic radiative refrigeration bulk material according to any one of claims 1-8, characterized in that, The method comprises the following steps: (1) mixing the weighed water glass-based binder and the C-F long chain modified micro-nano particles, introducing the nano-silica sol, and finally adding the curing catalyst, and stirring to form a homogeneous slurry; (2) vacuum injection molding the obtained homogeneous slurry under ultrasonic conditions, vacuum standing, room temperature curing, freezing, and demolding; (3) vacuum drying the demolded block material, and then polishing the surface of the block material to obtain the water glass-based full-life super-amphiphobic radiation refrigeration block material.

10. The method of claim 9, wherein, The vacuum injection molding in step (2) uses a vacuum degree of 0.06-0.08 MPa and a flow rate of 2-6 mL / min, and an ultrasonic power of 200-2000 W.

Citation Information

Cited By

  • High-weather-resistance electroless refrigeration coating as well as preparation method and application thereof

    CN122168060A